STUDI KOMPARATIF HASIL BELAJAR MELALUI MODEL PEMBELAJARAN PROBLEM SOLVING DAN PROBLEM POSING - Ida Nuri Fitria; Eddy Purnomo; Erlina Rupaidah (FKIP Unila, 2013)
This research know comparison study economics learning problem solving model students using learning problem posing model. The methods used experiment and comparative research. The study design used treatment by level,cluster random sampling. collect data used observation, interview, questionnaire , study post test. The test hypothesis uses Anava and T-test varian two ways. Based the results research: (1) there differences average studied economics among students using Problem Solving learning and Problem Posing model (2) average results studied economics students study using learning Problem Solving model higher than study using learning model Posing Problems students have positive attitude towards subject. (3) average results studied economics students study using learning Problem Solving model lower than study using learning Problem Posing students have negative attitude towards the subject . (4) there is no interaction between learning model and attitude students towards economic subjects. Penelitian ini bertujuan mengetahui perbandingan hasil belajar Ekonomi yang menggunakan model pembelajaran problem solving dengan pembelajaran problem posing. metode penelitian eksperimen dengan pendekatan komparatif . Desain penelitian treatment by level Teknik sampling cluster random sampling. Teknik pengumpulan data observasi, wawancara, angket tes hasil belajar. Pengujian hipotesis menggunakan rumus analisis varians dua jalan dan t-test dua sampel independen. Berdasarkan analisis data diperoleh: (1) terdapat perbedaan rata-rata hasil belajar antara siswa yang pembelajaranya menggunakan model pembelajaran Problem Solving dan model pembelajaran Problem Posing. (2) rata-rata hasil belajar yang pembelajaranya menggunakan model pembelajaran Problem Solving lebih tinggi dibandingkan menggunakan model pembelajaran Problem Posing bagi siswa yang memiliki sikap positif terhadap mata pelajaran (3) rata-rata hasil belajar pembelajaranya menggunakan model pembelajaran Problem Solving lebih tinggi dibandingkan yang pembelajaranya menggunakan model pembelajaran Problem Posing bagi siswa yang memiliki sikap negatif terhadap mata pelajaran.(4) tidak ada interaksi antara model pembelajaran dan sikap siswa terhadap mata pelajaran. Kata kunci: hasil, ps, pp, sikap